Nicotine Dependence among Adolescents Single and Dual Cigarette Users - Nawwal Alwani Mohd Radzi; Roslan Saub; Zamros Yuzadi Mohd Yusof; Maznah Dahlui; Sharol Lail Sujak (MDPI AG, 2021)
The prevalence of concurrent use of combustible and electronic cigarettes (dual-use) is on the rise among Malaysian adolescents. This study compares nicotine dependence among exclusive cigarette users, e-cigarette users, and dual adolescent users. A total of 227 adolescent smokers completed a self-administrated questionnaire with items based on Hooked on Nicotine Checklist (HONC) incorporated. Endorsement of at least one HONC item indicates nicotine dependence. Exhaled carbon monoxide readings and salivary cotinine data were also collected. Over half (52.9%) of the participants were exclusive e-cigarette users (EC). The prevalence of exclusive conventional cigarette smokers (CC) and dual users was 11.9% and 35.2%, respectively. Adolescents who have mothers with secondary school education were more likely to become addicted to nicotine (Adjusted Odd Ratio (aOR) = 2.72; 95% CI = 1.17-6.32). Adolescents' "mother's education" level predicted nicotine dependence. This highlighted the need to target families within the identified demography with a more supportive anti-tobacco program.